1973
DOI: 10.1002/cber.19731061015
|View full text |Cite
|
Sign up to set email alerts
|

1,3‐Dipolare Cycloadditionen, 70. Additionen des Benzonitriloxids an olefinische und acetylenische Dipolarophile

Abstract: Benzonitriloxid (2) bildet mit monosubstituierten Athylenen und Acetylenen 2-~soxazoline (3--10) und Isoxazole (29, 42), bei denen der Rest in der 5-Position erscheint. Ein Cemisch der beiden moglichen Orientierungsisomeren (17/18, 19/20) geht aus den Additionen an p-substituierte Styrole hervor. Abweichend verhielt sich p-Pyrrolidinostyrol, aus dem mit Benzonitriloxid nur 3,4-Diphenyl-S-pyrrolidin0-2-isoxazolin (22) cntsteht. Auch bci andcreii Enaminen diktiert die A m i d unktion ungeachtet sterischer Effekt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(36 citation statements)
references
References 29 publications
1
34
0
1
Order By: Relevance
“…Treatment of 21 and 22 with benzonitrile oxide, generated in situ from a-chlorobenzaldoxime, at 0°C in THF yielded the polymer-bound benzyl isoxazoles (23) and (24) respectively. Base cleavage of 23 and 24 as before, followed by esterification with CH2N2, gave solely methyl 3-phenylisoxazole-5-carboxylate (25) and only methyl 3,5-diphenylisoxazole-4-carboxylate (26) respectively in reasonable yield (Scheme 2). Although Huisgen et al (26,27) have shown that methyl propiolate and methyl phenylpropio'late reacted in a 1,3-dipolar addition addition reaction to give a 72:28 mixture of 25 and methyl 3-phenyl21n this paper we were particularly interested in the possible change in regioselecfiuity of adducts in going to solid phase Deils-Alder reactions from their solution analogs and were less interested in changes in enantioselectivity.…”
Section: 3-dipolar Cycloadditionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Treatment of 21 and 22 with benzonitrile oxide, generated in situ from a-chlorobenzaldoxime, at 0°C in THF yielded the polymer-bound benzyl isoxazoles (23) and (24) respectively. Base cleavage of 23 and 24 as before, followed by esterification with CH2N2, gave solely methyl 3-phenylisoxazole-5-carboxylate (25) and only methyl 3,5-diphenylisoxazole-4-carboxylate (26) respectively in reasonable yield (Scheme 2). Although Huisgen et al (26,27) have shown that methyl propiolate and methyl phenylpropio'late reacted in a 1,3-dipolar addition addition reaction to give a 72:28 mixture of 25 and methyl 3-phenyl21n this paper we were particularly interested in the possible change in regioselecfiuity of adducts in going to solid phase Deils-Alder reactions from their solution analogs and were less interested in changes in enantioselectivity.…”
Section: 3-dipolar Cycloadditionsmentioning
confidence: 85%
“…Base cleavage of 23 and 24 as before, followed by esterification with CH2N2, gave solely methyl 3-phenylisoxazole-5-carboxylate (25) and only methyl 3,5-diphenylisoxazole-4-carboxylate (26) respectively in reasonable yield (Scheme 2). Although Huisgen et al (26,27) have shown that methyl propiolate and methyl phenylpropio'late reacted in a 1,3-dipolar addition addition reaction to give a 72:28 mixture of 25 and methyl 3-phenyl21n this paper we were particularly interested in the possible change in regioselecfiuity of adducts in going to solid phase Deils-Alder reactions from their solution analogs and were less interested in changes in enantioselectivity. In addition, our base cleavage method is likely to cause cis-trans isomerization of the cycloadducts (22) and hence the original ratio of cis to trans isomers obtained in the solid phase reactions could not be accurately determined.…”
Section: 3-dipolar Cycloadditionsmentioning
confidence: 85%
“…A variety of synthetic methods has been elaborated for preparation of 2-isoxazolines, of which the most convenient and attractive route is the [2 + 3] dipolar cycloaddition of nitrile oxides to alkenes. 1 2-Isoxazolines can be easily reduced to several synthetically important compounds such as b-hydroxy ketones, b-hydroxy esters, a,b-unsaturated carbonyl compounds or iminoketones. 2 The nitrile oxides can be formed either by Huisgen method from aldoximes by chlorination and base-induced dehydrochlorination 1 or by dehydration of primary nitro compounds by phenyl isocyanates (Mukayama method) 3 or ethyl chloroformate (Shimizu method).…”
Section: Introductionmentioning
confidence: 99%
“…1 2-Isoxazolines can be easily reduced to several synthetically important compounds such as b-hydroxy ketones, b-hydroxy esters, a,b-unsaturated carbonyl compounds or iminoketones. 2 The nitrile oxides can be formed either by Huisgen method from aldoximes by chlorination and base-induced dehydrochlorination 1 or by dehydration of primary nitro compounds by phenyl isocyanates (Mukayama method) 3 or ethyl chloroformate (Shimizu method). 4 A key feature of the cycloaddition is the cis-stereospecificity -from E-alkenes 4,5-anti isomers are produced and from Z-alkenes 4,5-syn products are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…When irradiition of (30) in cyclohexane with light of 268-272nm is followed by uv spectroscopy, a-set of isosbestic points is recorded (see Fig. 4); curve a is the uv spectrum of (30) and b that of o-(3-phenyl-2H-azirinyl)-benzalaehyde (31). Although th~photocönversion of (30) to (31) is clean, the preparative scale photoreaction results in the complex proaucts from which (31) is obtained in 26% yield.…”
Section: Introduction and Historical Background Of Our Studiesmentioning
confidence: 99%